Poverty and its alleviation - Misra, S. N. (ed.) (New Delhi, 2005)
Poverty has become a global phenomena. Economic growth is considered a panacea for the reduction of poverty. Several poverty alleviation programmes beginning from Community Development Project to Swarnajayanti Swarozgar Yojana have been implemented with the express intention of lifting the BPL families to cross the poverty line. The programmes have failed to sustain the poor for long, although they have provided only short term palliatives. This book makes a definite contribution to the removal of poverty for providing a good standard of living in a sustainable manner.
Keywords: Poverty